Euroscepticism in the Berlusconi and Murdoch press. (November 2016) - Rowinski, Paul
A comparative analysis of Euroscepticism explores what it means in two nations and what is then articulated in specific newspapers. The theoretical terrain, Italy's and Britain's post-war relationships with the European Union, the countries' media structures and the specific context of Il Giornale (owned by Silvio Berlusconi's family) in Italy and The Times in the United Kingdom (owned by Rupert Murdoch) are mapped out. Some 21 interviews were conducted with relevant journalists and politicians (including reporters covering Europe for the aforementioned) offering further context. A critical discourse analysis of news stories and commentaries then spans the last decade. Although there is some Euroscepticism in Il Giornale, it has historically been localised, yet now seems to be growing in intensity. In The Times, however, the Euroscepticism conveyed is more pervasive and deeper. Its fact-based news can actually be very persuasive – ironically more akin to the commentary-laden news of Il Giornale – as the debate looms ahead of the planned 2017 UK referendum on European Union membership.